To be or not be (a goth): gothic origins and the construction of identity of iberian kingdoms (10th-12th centuries) - Gomes, Maria Joana (Guarecer. Revista Eletrónica de Estudos Medievais, 2019)
The genealogical connection of medieval kings of Spain to a specific people – the Visigoths – became among of the most important tools of legitimation used in the historiography written in the North-western Iberian Christian kingdoms. Chronicles and documents written under the direct command of king Alfonso III of Asturias affirmed the Gothic origins of the Asturian dynasty, an ideological current known as Neogothicism. In the same manner, and throughout the 11th-12th centuries, chronicles and documents issued by kings of León, successors of the Asturian kings, also used continuity with the Gothic past to consolidate the power of that dynasty. However, texts coming from other geographies, namely the territories of the recently formed kingdom of Portugal, opted for an alternative view of the past and of the origins of the realm, establishing other kinds of connections to validate the emergence of this new political entity. The aim of this paper is to show how continuity and discontinuity were used as an identity mark and a legitimation strategy in a set of texts written between the 10th and 12th centuries in Asturias, León and Portugal. DOI: http://dx.doi.org/10.21747/21839301/gua3a1